Turmeric-Associated Endophytic Bacteria with IAA-Producing and Phosphate-Solubilizing Activities as Growth-Promoting Agents - Siti Sholekha; Ahmad Ikhsanudin; Indriyani Indriyani; Kusuma Handayani; Nida Lidya Susanti; Ahmad Bintang Pamela (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2025)
White turmeric (Curcuma zedoaria) is one of the strategic bio-pharmaceutical plants commonly used as a cooking ingredient and as a family medicinal plant. In the Lampung region, turmeric ranks among the top five highest-yielding bio-pharmaceutical crops, making it an abundantly available commodity. This research aims to explore the endophytic bacteria present in turmeric and to investigate the functional abilities of the isolated strains. Endophytic bacteria are microorganisms that inhabit plant tissues and can act as plant growth promoters. In addition, these bacteria can solubilize phosphate, thereby supporting plant growth. Endophytic bacteria also produce the phytohormone IAA, which plays an important role in plant development. This study obtained three endophytic bacterial isolates from the leaves of white turmeric plants, namely KPD1, KPD2, and KPD3. Isolates KPD2 and KPD3 exhibited phosphate-solubilizing activity, as indicated by the formation of clear zones measuring 2.5 ± 0.58 mm and 4.0 ± 0.82 mm, respectively. In addition, all isolates were able to produce indole-3-acetic acid (IAA), with concentrations of 54.98 µg/mL (KPD2), 54.14 µg/mL (KPD3), and 25.05 µg/mL (KPD1). The abilities demonstrated by these endophytic bacterial isolates indicate their potential as plant growth-promoting bacteria (PGPB).